Theoretical study on the propagation of high impact energy in the rotor with local plastic deformation after blade off. (1st August 2023) - Yang, Cheng; Zhang, Dayi; Zhang, Qicheng; Zhao, Zhenyao; Zeng, Zhenkun
Highlights: The impact model of an inertia asymmetric rotor with blade off is derived and extends the stationary beam impact model. The modified criterion of the plastic hinge in the cylinder rotor is applied to consider the local plastic deformation. The gyroscopic moment can suppress the wave propagation characteristics of the impact energy for the rotor. The bending moment in the rotor is determined by gyroscopic moment and bending deformation. Abstract: A theoretical model of an elastic supported rotor system under impact by blade off is established based on d'Alembert principle. The gyroscopic moment of the blade-disk with asymmetrical inertia is considered in the dynamic model. The formation criterion of the plastic hinge in the cylinder rotor are derived and applied in the dynamic model to consider the local plastic deformation of the rotor with large deformation. This model extends the impact model of non-rotating beam with rigid support to the rotating beam and can describe the main mechanical properties of the rotor with blade off. The influence of the main factors, such as sudden unbalance, gyroscopic moment, geometric dimensions and concentrated mass, on the propagation of the impact energy in the rotor are analyzed. The gyroscopic moment can suppress the wave propagation characteristics of the impact energy in a rotating beam, resulting in an overall bending deformation, compared with the wave propagation characteristics of the impact energy in the non-rotating beam. Larger local concentrated mass can reduce the effect of impact, and increasing the cross-section size can significantly improve the plastic limit bending moment of the rotor. The variation of the bending moment in the low-pressure rotor is mainly determined by gyroscopic moment and bending deformation. Due to the constraint of the 1# and 2# pivots, the strain energy generated by fan blade off is mainly distributed in the shaft segment in front of the 2# pivot. Therefore, the impact resistance of this shaft segment should be improved to fulfill the safety design requirement of fan blade off failure.